Non-linear effect of water-table drawdown on water and nitrogen use efficiencies of Carex Muliensis Hand.-Mazz. In the zoige alpine wetland in tibetan plateau (Bangladesh Journal of Botany, 2025)
This study explored the water and N use efficiencies of Carex muliensis in the alpine wetland along water-table gradient in the Tibetan Plateau. It was found that the water-table drawdown significantly influenced leaf δ13C (water use efficiency, WUE) and C:N ratio (N use efficiency, NUE), and exhibited a non-linear correlation with WUE and NUE. The leaf δ13C initially increased and then decreased with the deceasing water table, with a threshold of ~40 cm. A trade-off was found between WUE and NUE in C. muliensis. Findings of this investigation offer insights into the relationship between the vegetation and hydrology, as well as, provide a scientific basis for the ecohydrological regulation and vegetation conservation in the alpine wetland.Bangladesh J. Bot. 54(3): 623-626, 2025 (September)